From Creativity to Innovation: An Entrepreneur Strategic Management for Business Development - Teguh Setiawan Wibowo; Nurul Hidayati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
Along with the development of the times, the competition of entrepreneurs will be adjusted to the development of existing businesses. The competition that is carried out does not only occur in the national market either through direct contact or digitally. However, it has covered a wider area such as global articles so that entrepreneurs are required to be able to face a lot of competition by continuing to improve the quality of products and services sustainably in order to realize future business development. In order to survive and win the competition, an entrepreneur needs strategic management and proper business development in starting and developing a business. In addition, the strategic management chosen must also have certain criteria such as creativity, where this creativity refers to a new combination that has a different quality of products and services than before. With this creativity, it is hoped that the new combination of products and services offered by entrepreneurs is something unique and refers to an innovation that can attract the attention of consumers and potential consumers. In this article, the discussion focuses on the strategic management of entrepreneurs for the development of their business by using creativity as an important point in creating an innovation in the products and services offered and can attract the attention of consumers and potential consumers.